Implementasi Sistem Absensi Guru Dan Tenaga Kependidikan Berbasis Geolokasi Dan Validasi Jam Kerja - Moh. Sukron; Moh. Rendy; Moh Haris Hamdani (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Improving the accountability and work discipline of teachers and educational staff requires an accurate, transparent, and tamper-resistant attendance system. This study implements a geolocation-based attendance system with work-hour validation at MI Misbahul Munir Sogaan Pakuniran Probolinggo to ensure that attendance is recorded within a predetermined location and time window. The system was developed using a Research and Development (R&D) approach comprising needs analysis, design, implementation, and testing. A web-based application was built using HTML5, PHP (CodeIgniter), and MySQL, leveraging the Geolocation API to obtain user coordinates and validate them against the school reference point and a predefined radius. The implementation results indicate geolocation accuracy of up to 3.2 meters in open areas; however, when used indoors, the deviation increased to 8 meters, suggesting a radius adjustment for certain zones. Functional testing using black-box testing across 15 main scenarios (authentication, check-in/check-out, and reporting) achieved a 100% success rate under normal conditions, and the system fulfilled approximately 95% of the requirements identified during the analysis stage. In addition, the system contributed to improved punctuality, reflected by a reduction in average lateness from 22.5 minutes to 6.8 minutes based on attendance recapitulation before and after implementation. With geolocation and work-hour validation, the system reduces opportunities for fraud, accelerates reporting, and enables real-time monitoring for the school principal. This study contributes a practical reference for adopting web-based geolocation attendance systems in primary Islamic schools and similar educational institutions